Experiences before the new normal by covid-19 in university. - Felipe-López, Reyna; Beristáin-García, Isabel; Guerrero-Castañeda, Raúl Fernando (Horizonte Sanitario, 2024)
Objective: to understand the experiences before the new normal in university students after the pandemic by COVID-19. Materials and methods: qualitative research, the units of meanings were built based on the moments of Martin Heidegger’s hermeneutic circle, for the selection of the participants, an intentional sampling was made of 16 university students of the nursing degree of a public university in the state of Oaxaca, where saturation of the data was reached, the phenomenological interview took place from March to May 2023 and were audiotaped, the research met the criteria of scientific rigor for qualitative research. Results: university students expressed having mental health problems due to confinement and social estrangement and in the face of the new normality has generated negative thoughts and feelings due to lack of communication, identifying the presence of their peers as negative, However, it is a new opportunity to start over and recognize life experiences with the help of a health professional. Conclusions: It is vital that educational institutions be able to develop appropriate strategies to improve the quality of life of university students by creating appropriate interventions to address the psychological problems that university students experience. Keywords: Mental health; COVID-19; nursing students; nursing.